Pilot proteomic analysis of immune dysregulation in dengue with prior SARS-CoV-2 infection - Cruz-Altamirano, Elizabeth; Mayoral-Chávez, Miguel Angel; Ramírez-Palacios, Luis Román; Quirino-Vela, Luz Maria; Cruz-Hernández, Diego Sait; Aguilar-Ruíz, Sergio Roberto; Alpuche, Juan (Frontiers in Immunology, 2026)
BackgroundIn regions where dengue and COVID-19 co-circulate, cross-reactive antibodies elicited by SARS-CoV-2 may exacerbate dengue severity. This exploratory, cross-sectional, observational pilot study evaluated whether prior SARS-CoV-2 exposure modulated dengue pathogenesis through proteomic profiling and in vitro assays, identifying putative biomarkers and immune pathways for further validation.MethodsEighteen participants from Oaxaca, Mexico, were prospectively stratified into four cohorts: healthy controls (CG), dengue with anti-SARS-CoV-2 IgG (NS1/SARS_IgG), dengue with both anti-SARS-CoV-2 and anti-dengue IgG (NS1/SARS-DENV_IgG), and dengue with anti-dengue IgG only (NS1/DENV_IgG). The serum levels of IL-6 and C-reactive protein (CRP) were quantified, and proteomic analysis was performed using label-free Liquid Chromatography-Tandem Mass Spectrometry (LC–MS/MS). In vitro antibody-dependent enhancement (ADE) assays were performed using the DENV-1 and K562 cells.ResultsThe NS1/DENV_IgG group exhibited the most severe clinical presentation, including 39 °C fever and 50% thrombocytopenia. In contrast, the NS1/SARS-DENV_IgG group presented milder symptoms. IL-6 and CRP concentrations peaked in the NS1/SARS_IgG group (18.3 ± 15.6 pg/mL and 51.6 ± 29.6 mg/L, respectively). Proteomic profiling identified 279 high-confidence proteins and 18 differentially expressed proteins (DEPs). The NS1/SARS-DENV_IgG group showed enrichment in the complement/coagulation pathways (p = 0.016) and TGF-β signaling (p = 0.022). DEPs, including thrombospondin-1 and PRG2, have been implicated in Th2 polarization and ADE-like immune dysregulation. ADE assays confirmed that anti-SARS-CoV-2 serum enhanced DENV replication in vitro.ConclusionsPrior SARS-CoV-2 exposure may potentiate dengue severity via cross-reactive antibody-mediated immune modulation, skewing toward Th2 responses and enhancing viral replication. These findings suggest novel candidate biomarkers for stratifying the dengue risk in co-endemic regions. However, the study’s exploratory nature, small cohort (n = 18), pooled proteomic methodology, and limited clinical characterization necessitate validation in larger longitudinal studies.